MUSTIKA ARUM SUNTINGAN TEKS DAN TERJEMAHAN - , REKI GUMELAR; , Drs. Soeharto Mangkusudarmo, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Manuscript containing Mustika Arum text a collection of Gendungan community, Temanggung. Text in the manuscript that contains the teachings of Islam Javanese mysticism. The teachings presented in the language prose. Therefore, this text can be classified as wirid text. The mystical teachings of Islam in this text reveal about the origin of all life, the Prophet Muhammad, and the relationship between Man and God. This study presents the editing text and translation. Editing used are diplomatic text method and reading improvement. Translation used are the literal translation and free translation.